Elaboración de herramientas informáticas de visualización y análisis sísmico para la plataforma virtual del GRISSUTPL - Erreyes Vaca, Jean Dario (2018)
Abstract:Knowledge of the seismicity of a region is necessary for any calculation or mitigation plan of its effects and is essential for the development of building codes and seismic scenarios, for this reason it is important to know the characteristics of the seismicity of an area. It's show the methodological process carried out for the elaboration of computer tools for real-time seismic visualization and analysis for the web page of the Seismic Engineering and Seismology Group of the UTPL. The data used were collected from different sources and databases of seismic records worldwide. Through DRUPAL software, a new menu called Seismic Observatory of Ecuador (OSSE) was developed, which facilitated the visualization of the implemented contents such as: videos, seismic recordings, reports and infographics related to seismic engineering. The software allowed the presentation of data on seismic events occurring at the national and international levels. In addition, seismic reports, quarterly, half-yearly and annual reports were prepared during the elaboration of the present work (September 2017-September 2018)